Out of the black land eaudiobook - Greenwood, Kerry (Blackstone Audio, Inc., and Buck 50 Productions, LLC, 2013)
Egypt during the eighteenth dynasty is peaceful and prosperous under the joint rule of the pharaohs Amenhotep III and IV—until the younger pharaoh begins to dream new and terrifying dreams. Ptah-hotep, a young peasant boy studying to be a scribe, wants to live a simple life in a hut on the Nile River with his lover Kheperren and their dog Wolf—until Amenhotep IV appoints him as royal scribe. How long will Ptah-hotep survive there, surrounded by bitterly envious rivals and enemies? The child princess Mutnodjme sees her beautiful sister Nefertiti married off to the impotent young Amenhotep. But Nefertiti must bear royal children, so the ladies of the court devise a shocking plan. Kheperren, meanwhile, serves as scribe to the daring teenage general Horemheb. But while the pharaoh's shrinking army guards the land of the Nile from enemies on every border, a far greater menace impends, for the newly renamed Akhnaten, not content with his own devotion to one god alone, plans to suppress the worship of all other gods in the Black Land. Members of his horrified court soon realize that the pharaoh is not merely deformed but irretrievably mad and that the biggest danger to the empire is within the royal palace itself.